OFDM transmission scheme with subcarrier supply index modulation - Yi GUO; Yiqing WANG; Yuanyuan FAN; Gang LIU (Tongxin xuebao)
To address the drawback that subcarrier activation pattern (SAP) of the orthogonal frequency division multiplexing with index modulation (OFDM-IM) cannot match the binary numbers which affects the system performance, the orthogonal frequency division multiplexing with subcarrier supply index modulation (OFDM-SSIM) transmission scheme was proposed.The index utilization of the system was improved and the spectral efficiency (SE) of the system was enhanced by adding the supply index.Also, as the subcarrier activation pattern of the proposed scheme match the binary numbers, low complexity log-likelihood ratio (LLR) detection was made easy to adopt and bit error rate (BER) performance was maintained good.Theoretical analysis and simulation results show that the proposed scheme effectively improves the SE and BER performance over classical OFDM-IM scheme in additive white Gaussian noise (AWGN) channels and Rayleigh fading channels.